2013
DOI: 10.1155/2013/697390
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Propolis for Its Biological and Chemical Compositions and Its Botanical Origin

Abstract: Propolis is the generic name given to the product obtained from resinous substances, which is gummy and balsamic and which is collected by bees from flowers, buds, and exudates of plants. It is a popular folk medicine possessing a broad spectrum of biological activities. These biological properties are related to its chemical composition and more specifically to the phenolic compounds that vary in their structure and concentration depending on the region of production, availability of sources to collect plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
333
0
28

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(363 citation statements)
references
References 91 publications
2
333
0
28
Order By: Relevance
“…Propolis contains a variety of compounds, some of which are terpenes, flavonoids and other phenolics (Marcucci, 1995;Bankova et al, 2000). Previous studies have also shown that the chemical composition of propolis varies with geographical origin, botanical source and bee species (Bankova, 2005;Silici and Kutluca, 2005;Salatino et al, 2011;Fernandes-Silva et al, 2013;Toreti et al, 2013). Propolis serves as a beehive protective barrier against microbial contamination and a sealant for unwanted small gaps in the beehive (Bankova, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Propolis contains a variety of compounds, some of which are terpenes, flavonoids and other phenolics (Marcucci, 1995;Bankova et al, 2000). Previous studies have also shown that the chemical composition of propolis varies with geographical origin, botanical source and bee species (Bankova, 2005;Silici and Kutluca, 2005;Salatino et al, 2011;Fernandes-Silva et al, 2013;Toreti et al, 2013). Propolis serves as a beehive protective barrier against microbial contamination and a sealant for unwanted small gaps in the beehive (Bankova, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…It is collected by bees from flowers, buds, and exudates of plants and is known to have a broad spectrum of biological properties (Mello and Hubinger, 2012;Toreti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The quality and amount of propolis produced are linked to seasonal variations, methods of collection (Inoue et al, 2007;Toreti et al, 2013), geographical diversity, plant sources, and bee species (Mello and Hubinger, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations